California bearing ratio tests of enzyme-treated sedimentary residual soil show no improvement - Khan, Tanveer Ahmed; Mohd. Raihan Taha,; Firoozi, Ali Asghar; Firoozi, Ali Akbar (Penerbit Universiti Kebangsaan Malaysia, 2017)
Environmental concerns have significantly influenced the construction industry regarding the identification and use of environmentally sustainable construction materials. In this context, enzymes (organic materials) have been introduced recently for ground improvement projects such as pavements and embankments. The present experimental study was carried out in order to evaluate the compressive strength of a sedimentary residual soil treated with three different types of enzymes, as assessed through a California bearing ratio (CBR) test. Controlled untreated and treated soil samples containing four dosages (the recommended dose and two, five and 10 times the recommended dose) were prepared, sealed and cured for four months. Following the curing period, samples were soaked in water for four days before the CBR tests were administered. These tests showed no improvement in the soil is compressive strength; in other words, samples prepared even at higher dosages did not exhibit any improvement. Nuclear magnetic resonance (NMR) spectroscopy tests were carried out on three enzymes in order to study the functional groups present in them. Furthermore, X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM) tests were executed for untreated and treated soil samples to determine if any chemical reaction took place between the soil and the enzymes. Neither of the tests (XRD nor FESEM) revealed any change. In fact, the XRD patterns and FESEM images for untreated and treated soil samples were indistinguishable.